Thinking theologically about mass incarceration : biblical foundations and justice imperatives - Kireopoulos, Antonios (New York : Paulist Press, 2017)
"From 2014 to 2016, under the auspices of the National Council of Churches, the contributors to this volume participated in a multilateral dialogue on the question of mass incarceration, working with three themes: Biblical foundations, how theology informs justice, and how justice informs theology. This book is the fruit of those dialogues"--Cover.
Preface: The churches and the incarceration epidemic / Antonios Kireopoulos, Mitzi J. Budde, and Matthew D. Lundberg. -- I. The situation today: 1. An epistle to the American church : "set the captives free" / Michael C. Richardson -- 2. Christian unity for a fractured society : the problem of mass incarceration for the churches / Antonios Kireopoulos -- 3. On incarceration : for the sake of our shared future / Michael Redi Trice -- 4. White supremacy and the church : how white Christians created and perpetuate the ideology of white supremacy / Douglas A. Foster -- 5. On the other side of the divide / Reginald D. Broadnax and Kenneth Q. James. -- II. Biblical reflections: 6. Seventy times seven : offenders, victims, and Jesus' extravagant call to forgive / Gayle Gerber Koontz -- 7. Considering issues of mass incarceration through the lens of the Beatitiudes / Shirley Paulson -- 8. How Paul's transformation addresses mass incarceration today / Madelon Maupin -- 9. The revelation to John, prisoner on the island of Patmos / Don Thorsen. -- III. Theological explorations: 10. La Nueva encomienda : the church's response to undocumented migrants as mass incarcerated / Loida I. Martell -- 11. A beginning understanding of the nature of God's justice and the U.S. justice system / W. Scott Axford -- 12. Crying out in the wilderness : proclamation, empowerment, and justice -- 13. Mass incarceration, capital punishment, and penal atonement theories : correlation, or something more? / Greg Carey -- 14. The prophetic cry for justice : a Pentecostal response to the racism of mass incarceration / Peter Althouse -- 15. "Get on the cart!" : Wesleyan discipleship in an age of endemic incarceration / Benjamin Hartley, Glen Alton Messer II, and Kirsten Sonkyo Oh. -- IV. Ecumenical considerations: 16. The problem of empty pews : mass incarceration as a church-dividing issue / Matthew D. Lundberg -- 17. Common moral ground : can ethics be church uniting? / Mitzi J. Budde. -- V. Experiential and practical perspectives: 18. The voices of too many people are silenced / Kenneth Q. James -- 19. White privilege : my journey with segregation / Frank Lesko -- 20. Preaching to bridge peoples on issues of race / Joyce Shin -- 21. Lord, make my troubles light : a historical and spiritual reflection on Quaker work in prisons / Philip Caroom, Rachel Guaraldi, and Ann K. Riggs -- 22. An introductory prophetic cry against inequities in the American mass incarceration system / David J. Fekete. -- Contributors.
Print version record and CIP data provided by publisher; resource not viewed.
Added to collection customer.56279.3 - Master record variable field(s) change: 072
Keywords: Imprisonment -- Religious aspects -- Christianity; Discrimination in criminal justice administration -- United States; Social justice -- United States; Discrimination in criminal justice administration; Imprisonment -- Religious aspects -- Christianity; Social justice; United States; RELIGION / Christian Life / Social Issues; RELIGION / Christianity / General; Electronic books